(untitled) (Experimental biology, 2015)
One of the conditions for sustainable development of Aktobe oblast is to ensure environmental safety, prevention of the risk impact on the health of the population of negative environmental factors. In study the environmental risk assessment for the health of population were established, the results of metal accumulation in tissues of children Aktobe were given. The targets for public health, environmental quality, the level of risk to public health were established.